Managing Muslim-Christian conflicts in Northern Nigeria: a case study of Kaduna State - Yusuf, Bilkisu (Islam and Christian-Muslim relations, 2007)
This article sets out to identify the causes of Christian–Muslim conflicts in Northern Nigeria and suggest strategies for peaceful co-existence among the adherents of the two religions. It is based on in-depth interviews with the community and religious leaders and a survey of media coverage of the crises. The article examines the sudden upsurge of violent conflicts between Christians and Muslims in Northern Nigeria in general and Kaduna State in particular. Analysts posit that these conflicts arise from clashes of values and claims to scarce resources, power and status. The article examines how non-Muslims view the emirate system of administration with its Islamic origin, the Sharica system of law operating in the Northern States, and the effects of these on Christian–Muslim relations.